PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII - Arnof, M. Nafs (Departemen Matematika, 2023)
Mathematical communication skill is one of learning objective in mathematics. However, in reality the communication of mathematical skills by class VIII student at SMPN 3 Lubuk Basung are still lack. One solution to increase mathematical communication skills is the use a Student Teams Achievement Divisions (STAD), a model of cooperative learning. The study purpose was to determine whether the mathematical communication skill of studentsworking with the STAD model are better than those of students using direct learning. This study type was a researchin quasy-experimental design with posttest only control group design. The research data were obtained by test of mathematical communication skills. Data analysis concluded that students using the STAD model performed better in mathematical communication skills than those using direct learning. Keywords–Cooperative Learning, Student Teams Achievement Divisions, Mathematical Communication Skills.